TESTING THE PERFORMANCE OF TWO DIFFERENT DIGESTERS FOR BIOGAS PRODUCTION FROM HOUSEHOLD WASTE CO-DIGESTED WITH COW DUNG (FUDMA JOURNAL OF SCIENCES, 2024)
The research was carried out at Mechanical Engineering Department, Federal University Dutsin-Ma, Katsina State, Nigeria. Different researches of bio-digesters have been conducted for biogas production but the physico-chemical properties of wastes, constituents of biogas and volume of digesters were not considered in previous research which resulted to poor performance of digesters by producing low flame. Hence the physico-chemical properties of wastes were determined, constituents of biogas were determined and volumes of digesters were considered for this research work so as to have effective performance of the digesters. This study involved  the performance evaluation of two different digesters for the production of biogas from household Wastes co-digested with cow dung to select the best digester among the two suitable for household used. Two different digesters each of 5.5 litres and 90 litres were used for testing the performance of digesters using household Wastes co-digested with cow dung in which anaerobic digestion process at both mesophilic and thermophilic temperatures were employed.After the physico-chemical properties of wastes test, analysis of biogas constituents, Ventilation test and flammability test of both digesters were conducted.The highest volume of biogas produced for Digester 1 was 115 liters/day within a period of 15days and 2537 liters/day within a period of 28days for Digester 2.The Ventilation and flammability tests were conducted of both digesters in which Digester 1 passed Ventilation test and failed flammability test.The Digester 2 passed both Ventilation and flammability tests.The research concluded that, the Digester 2 was more effective  because of large volume of Digester...
Keywords: Biogas; Digester; Wastes; Household; Cow dung